Recovery of Phenolic Compounds with Antioxidant Capacity Through Solid-State Fermentation of Pistachio Green Hull - Andrés Javier Ordoñez-Cano; Ulises Ramírez-Esparza; Fernando Méndez-González; Mónica Alvarado-González; Ramiro Baeza-Jiménez; Leonardo Sepúlveda-Torre; Lilia Arely Prado-Barragán; José Juan Buenrostro-Figueroa (Microorganisms)
Pistachio green hull (PGH) represents the non-edible fraction obtained after the seed is harvested and is an important source of phenolic compounds. Solid-state fermentation (SSF) is a viable biotechnological and economical technique for extracting phenolic compounds. This study aimed to evaluate the SSF with Aspergillus niger GH1 to recover total phenolic compounds (TPC) with antioxidant capacity (AC) from PGH. For this, the time of higher TPC and AC (DPPH [2,2-diphenyl-1-picrylhydrazyl], ABTS [2,2-azinobis-(3-ethylbenzothiazoline-6-sulfonate)], FRAP [ferric reducing antioxidant power]) was selected. Then, moisture, inoculum concentration, and aeration rate were evaluated. A. niger GH1 was able to grow and colonize the PGH, with the higher value of TPC (23.83 mg/g of dry mass (gdm)) obtained after 24 h of culture, which significantly correlated with AC (Pearson’s R = 0.69). Moisture and aeration rate were the main factors influencing TPC. The highest values for both TPC and AC were achieved in treatment 8 (60% moisture, 5 × 106 spores/mL, and 1 L/Kgwm min), resulting in a 129% and 1039% increase, respectively. Gallic acid 4-O-glucoside and geranine were identified in the PGH extracts using high-performance liquid chromatography coupled with mass spectrometry. The SSF provides eco-friendly alternatives for releasing bioactive compounds from PGH, adding value to this waste.